Meta-analysis of altered gray matter volume in acute lymphoblastic leukemia patients’ postchemotherapy via the AES–SDM - Xuelian Zong; Huiping Liu; Xiaoyun Zhao (European Journal of Medical Research)
Abstract Background Voxel-based morphometry (VBM) reveals diverse alterations in gray matter volume in acute lymphoblastic leukemia (ALL) patients after chemotherapy. However, the reported results are inconsistent. Therefore, our objective was to conduct a meta-analysis to synthesize findings from existing VBM studies and identify consistent patterns of altered gray matter volume in ALL patients post-chemotherapy. Materials and methods A systematic search was conducted across PubMed, Web of Knowledge, Embase, Google Scholar, and CNKI for VBM studies that compared ALL patients post-chemotherapy with healthy controls (HCs) up to April 1, 2024. Significant cluster coordinates were extracted for comprehensive analysis. Results We included 7 studies involving 143 ALL patients post-chemotherapy and 140 HCs. ALL patients who underwent chemotherapy presented decreased gray matter volume in the left caudate nucleus, left calcarine fissure/surrounding cortex, left precentral gyrus and right anterior thalamic projections. Jackknife sensitivity analysis validated the robustness of these findings. Conclusions This meta-analysis revealed consistent gray matter volume alterations in ALL patients post-chemotherapy, emphasizing the need to explore their underlying mechanisms and long-term effects on cognitive and neurological health.